Improving Technological Performances of Ball Clays: A Case-study from Patagonia (Argentina) - Zanelli, Chiara (2011)
Innovation in the ceramic tile industry is stressing properties like powder flowability and ability to toughen green tiles, so turning technological requirements of ball clays ever stricter in terms of plasticity, dispersion in water, rheological properties, workability in the green state, refractoriness and firing colour. Technological performance of ball clays have been improved by taking as benchmark the highest quality raw materials on the market. The mineralogy, plasticity, methylene blue index and ceramic behavior of the Patagonian ball clays are analogous to those of European clays, but improvement is needed to approach the highest quality materials. On this basis, four Patagonian deposits were selected and their characteristics enhanced by adding highly plastic corrective clays targeted on the benchmark. Porcelain stoneware formulations, containing improved ball clay mixes, were experimented at both laboratory and industrial scale. The improved ball clays behave like the best raw materials currently used, although modest changes occur in the mechanical properties, water absorption and whiteness of the fired products.